Use of local corticosteroid injection in the treatment of plantar fasciitis - Sah, Deb Narayan; Sharma, Bishnu Dev (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Plantar fasciitis is a common pathological condition that affects the hind foot. Management of plantar fasciitis employs use of various non-surgical and surgical treatment methods. The aim of this study was to evaluate the efficacy of steroid injection in the treatment of plantar fasciitis in adults.Materials and Methods: From January 2016 to June 2017, fifty patients aged >18 years with plantar fasciitis symptomatic for three months or more were injected with a single dose of methylprednisolone acetate with 2% lignocaine. Assessment was done using visual analogue scale (VAS) and foot function index (pain sub-scale). Patients were followed-up for a period of 6 months.Results:There was significant reduction in VAS score and improvement in foot function index at 1 and 3 month follow-up (p